2014
DOI: 10.1063/1.4904998
|View full text |Cite
|
Sign up to set email alerts
|

Microsized structures assisted nanostructure formation on ZnSe wafer by femtosecond laser irradiation

Abstract: Micro/nano patterning of ZnSe wafer is demonstrated by femtosecond laser irradiation through a diffracting pinhole. The irradiation results obtained at fluences above the ablation threshold are characterized by scanning electron microscopy. The microsized structure with low spatial frequency has a good agreement with Fresnel diffraction theory. Laser induced periodic surface structures and laser-induced periodic curvelet surface structures with high spatial frequency have been found on the surfaces of microsiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…As known, the ablation 3 Journal of Nanomaterials threshold for ZnSe is about 0.7 J/cm 2 [22]. The LIPSS parameters obtained in our experiments correlate with the data of the previous studies [14,15,17,23].…”
Section: Peculiarities Of Lipss Formation On the Znse Surfacesupporting
confidence: 88%
See 2 more Smart Citations
“…As known, the ablation 3 Journal of Nanomaterials threshold for ZnSe is about 0.7 J/cm 2 [22]. The LIPSS parameters obtained in our experiments correlate with the data of the previous studies [14,15,17,23].…”
Section: Peculiarities Of Lipss Formation On the Znse Surfacesupporting
confidence: 88%
“…Based on the Drude model, modified femtosecond laser-excited refractive index n * for ZnSe is lower than that for untreated material. Thus, Wang et al [23] obtained for the laser-treated ZnSe the HSFL period of 200 ± 10 nm. The values of HSFL periods obtained in our [32][33][34][35].…”
Section: Peculiarities Of Lipss Formation On the Znse Surfacementioning
confidence: 99%
See 1 more Smart Citation
“…The period of the formed structure is typically larger than halfwavelength, λ∕2, with a strong dependence on the angle of incidence [4,5]. However, under femtosecond (fs) laser irradiation, periods slightly smaller than the laser wavelength [therefore, subwavelength structures (SWS)] [3,4], as well as deep-subwavelength structures (DSWS) [6][7][8][9][10][11] with periods considerably smaller than λ∕2, were observed on transparent materials and semiconductors. Up to now, these two types of surface structures have become a universally observed feature in the fs laser multipulse ablation [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…16 Wang et al reported a micro/nanopatterning by fs laser irradiation through a pinhole. 17 Two of the essential challenges of laser induced surface micro/nanostructures are the control of the morphologies of the individual objects and the control of their arrangements.…”
mentioning
confidence: 99%